Respuestas

2013-07-08T16:16:42+02:00
A.(3^2)^4 = 3^8
b.[(4)
^3]^2 = (2^2)^6 = 2^12
c.[(-1)
^5]^3 = (-1)^15
d.[(-9)
^4]^3 = (- 3^2)^12 = (- 3)^24
e.[(-5)
^2]^2 = (-5)^4
f.[(-10)
^2]^5 = (-10)^10
g.[(-7)
^2]^2 = (-7)^4
h.[6
^2]^4 = 6^8
i.[(-9)
^4]^0 = (-3^2)^0 = (-3)^0
j.(5
^3)^2 = 5^6
k.[(-6)
^3]^2 = (-6)^6
l[(-2)
^5]^4 = (-2)^20
  • Usuario de Brainly
2013-07-08T16:20:33+02:00
Lo unico que tienes que haces es multiplicar los exponentes que tiene
a.3^8
b. 4
^6
c.-1
^15
d.-9
^12
e.-5
^4
f.-10
^10
g.-7
^4
h.6
^8
i.-9
^0
j.5
^6
k.-6
^6
l  - 2
^20

espero hayas entendido